Pattern of Thyroid Disorders in a Tertiary Care Centre of a High-Altitude Region of Nepal: A hospital-based retrospective study - Tirtha Narayan Sah; Anuraj Anu; Binamra Bista (Journal of Karnali Academy of Health Sciences)
Background: Millions of people globally suffer from thyroid disorders, with over half of them are unaware of their conditions. Untreated, these disorders can lead to severe health complications such as heart problems, pregnancy complications, goiter, bone health issues, etc. Jumla, a high-altitude Himalayan region in Nepal, includes iodine-deficient areas, making it prone to thyroid disorders. This study aimed to identify the prevalence and pattern of thyroid disorders in this region.